Are we closer to being able to select patients with node-positive hormone receptor-positive breast cancer who can safely omit chemotherapy?. (March 2022) - Taylor, Caitlin; Meisel, Jane; Kalinsky, Kevin
The treatment of hormone receptor-positive, HER2-negative breast cancer has become increasingly individualized, thanks to the development of genomic testing. Gene expression assays provide clinicians and patients with both prognostic and predictive information regarding breast cancer recurrence risk and potential benefit of chemotherapy. While the ability to tailor therapy based on clinicopathologic and genomic factors has enabled a growing number of women to forego chemotherapy, several questions remain regarding how best to apply genomic assay results across varying subgroups of women. Here, we review the role of genomic assays for patients with both lymph node-negative and lymph node-positive breast cancer, and how these assays may help us more precisely select patients with hormone receptor-positive (HR+), human epidermal growth factor receptor 2-negative (HER2−) breast cancer with or without lymph node involvement who can safely omit chemotherapy in the future.